Effect of SiO2 and Al2O3 nanoparticles on wear resistance of PMMA acrylic denture teeth - Helal, Mohamed A (2020)
Objective: This study aimed to evaluate the wear resistance of acrylic denture teeth containing silicon dioxide (nano-SiO2) and aluminum dioxide (nano-Al2O3) nanoparticles. Material and Methods: Poly methyl methacrylate (PMMA) denture tooth material was used to denture tooth material was used to fabricate 84 specimens (n=10) containing nano-SiO2 and nano-Al2O3 in concentrations 0.1wt%, 0.3wt%, and 0.5wt% of acrylic powder. A two-body wear testing machine and digital microscope were used to measure the changes in weight loss and surface roughness respectively. One-way ANOVA and pair-wise Tukey’s post-hoc tests were used for data analysis (? = 0.05). Results: Nano-SiO2 modified teeth material demonstrated a significant increase in weight loss in comparison conventional artificial acrylic teeth material (p ? 0.05) while nano- Al2O3 modified teeth material demonstrated non-significant increase in weight loss except for 0.5% subgroup (p ? 0.05). There is no significant differences regarding roughness change after wear simulation among all tested groups (p > 0.05). Conclusion: Nano-Al2O3 nanoparticles exhibit less negative effect than nano-SiO2 so; it could be used with caution if necessary.KeywordsAcrylic denture teeth; Al2O3 nanoparticles; SiO2 nanoparticles; wear resistance; surface roughness.